Neuropsychological Assessments of Dementia in Down Syndrome and Intellectual Disabilities (Springer International Publishing, 2018)
This fully updated and expanded second edition of a successful book reviews the most important neuropsychological measures currently used in the assessment of dementia by the principal clinicians and researchers associated with the tests. Several clinicians and research workers, who have been at the forefront in developing the tests in question, provide clear practical guidance on the scope of each test, use in research, as well as an analysis of their accuracy and limitations. The international contributors have brought together a concise and practical guide on the role of neuropsychological testing to support the dementia assessment. Neuropsychological Assessments of Dementia in Down Syndrome and Intellectual Disabilities, Second Edition is an essential reference for all those working in the field of dementia and intellectual disabilities.